Achieving food security while switching to low carbon agriculture - Fan, Shenggen; Ramirez, Ana (AIP Publishing, 2012)
The increase of greenhouse gas (GHG) emissions is irreversibly raising the earth’s temperature, with its effects already being seen across the world, with higher frequency and intensity of extreme weather events and natural disasters. Agriculture is extremely vulnerable to these climatic changes, and in most regions of the world, productivity and yields are likely to suffer from shifting seasons and heightened weather variability. These changes could lead to higher food prices for the main food crops and undermine global food security. However, agriculture is also part of the problem of climate change. Together with land-use change and deforestation, it is a large contributor to global GHG emissions. In order to face the challenge of climate change, the carbon intensity of agriculture must be reduced in a way that will not compromise the food security of poor people. With the right innovations, investments, and policy incentives in place, low GHG emission agriculture practices can help mitigate the effects of climate change, reduce emissions while contributing to food security. Governments and donors must ensure that the switch to low GHG emissions technologies and practices—referred to as low carbon throughout the article, is done in a way that is pro-poor and that meets smallholders’ and women’s needs.